Factors Affecting The Effectiveness of Application Local Regulation of Cigarette Free Areas in Puskesmas Balangan District - Herry Rusandy; Ruslan Muhyi; Erida Widyamala; Husaini Husaini; Lenie Marlinae (Jurnal Berkala Kesehatan, 2021)
Indonesia is the third country of smokers in the world. It increases disease and death by 50% in developing countries.  WHO launched "No Smoking Areas" in public places. The purpose of this study was analyzing the socialization, budget, policies, and compliance in the effectiveness of implementing the Regulation on KTR in Balangan Regency. The research subjects were male health services officers in 10 accredited Puskesmas in Balangan Regency with total of 59 people, which determined sample size of 42 people. The method used cross-sectional. Data were analyzed by chi square and logistic regression. The results are there is an effect of socialization on effectiveness of implementing the Regional Regulation on KTR (0.008); there is an influence of budget on effectiveness of implementing Regional Regulation on KTR (p = 0.080); there is a policy influence on effectiveness of the implementation of Regional Regulation on KTR (0.003); there is an effect of compliance with effectiveness of implementing Regional Regulation on KTR (0.016); The most dominant influence is policy with a value of p = 0.004 and exp (B) = 43.530. The conclusion is there is an effect of socialization, policy and compliance with the effectiveness of implementing the Perda KTR with the dominant variable is policy.